Use of Molecular Genetic Methods to Reduce the Risk of Incorrect Identification of Fish Strains in Brazilian Aquaculture - Deoclécio da Silva, Luana Maria; do Prado, Fernanda Dotti; Hashimoto, Diogo Teruo; Senhorini, José Augusto; Foresti, Fausto; Porto-Foresti, Fabio (Frontiers in Genetics, 2021)
The identification of fish species using traditional methods is generally based only on morphological characteristics and these methods are currently under review. This kind of identification of hybrid fishes solely based on their morphologies may be unreliable, especially when the samples include juveniles and post-F1 lineage fishes. Therefore, in the present study, we used molecular markers to accurately identify the fish species of economic interest that are used as materials in the projects developed in research institutions. We evaluated six lots of fishes sampled from different research centers, containing a total of 84 specimens acquired from private fish farms that were considered to be the representatives of pure species. Genetic analyses of all the specimens revealed that, globally, 22 samples (26.2 %) were interspecific hybrids, while 20 (90.9%) samples were surprisingly characterized as post-F1 hybrids. This result confirms that hybrids are sold in markets without adequate labeling and also indicates the lack of proper control of the commercialization and management of stocks and products in fish farms. In addition, we determined that molecular diagnosis was an extremely effective and necessary method to test the reliability of biological materials currently used in scientific research.